Show Me, Tell Me: An Investigation Into Learning Processes Within Skateboarding as an Informal Coaching Environment - Collins, Rosie; Collins, Dave; Carson, Howie J. (Frontiers in Psychology, 2022)
Coach education is a learner-centred process, which often fails to consider the preferences of the consumer. Historically, research into performers’ experiences of coaching have been influenced by the social constructivism of learning: in short, an expressed preference for what the performer has experienced as determined by their coach, rather than their own personal preferences. Therefore, this research used skateboarding as a natural laboratory in order to explore the current practices and preferences of performers in a coach-free environment. Ninety-one skateboarders from parks in the UK and New Zealand offered information relating to their current learning practices, how they learnt about learning, and how the top-level performers in their environment were differentiated. Findings suggest that a number of coaching tools are used by performers, which are closely aligned with a more traditional, cognitive view of coaching (e.g., demonstration, drills, error usage). Results also suggest that performers deployed a number of cognitive skills (imagery, analogy, understanding) to enhance storage of a movement as an internal representation. Finally, in the absence of formal coaching, performers use their knowledge of learning to appoint informal leaders. Implications for practice are discussed.